Oral health behaviors, dental injuries and mouthguard awareness among a sample of Portuguese athletes: a cross sectional study. - Luís Azevedo; David Simões Martins; Joana Fialho; Nélio Veiga; André Correia; Peter Fine (Universidad de Concepción., 2019)
Aim: To determine the oral health behaviors, the prevalence of dental injuries, the level of information about first-aid procedures in the case of dental avulsion and the mouthguard awareness in a sample of Portuguese athletes. Materials and Methods: Cross-sectional research among 1,048 athletes from the district of Viseu, Portugal. A self-administered questionnaire included demographic data and questions about: I) oral hygiene habits, II) occurrence of orofacial trauma, III) use of mouthguards and IV) athletes' knowledge regarding first-aid management in case of dental avulsion was given. The comparison between different variables was made by Chi-square test with level of significant set at p-value ≤0.05. Results: The mean age of the sample (76.24% male) was 18.14±8.17 years. Overall, the results demonstrated a low use of dental floss (25.48%) and a high number of athletes (21.94%) that had not visited a dentist in more than a year. The prevalence of dental trauma was 5.06% and the most common dental injuries experienced by athletes were crown fractures (60.38%). Nearly half of the participants (45.23%) reported not knowing how to act following a dental avulsion. The rate of mouthguard use was very low (9.73%). There was a significant relationship between the prevalence of dental injuries and the use of mouthguards (p=0.000; Cramér's V=0.145). Conclusion: The prevalence of dental trauma in our population was low. A low number of athletes use a mouthguard and there is a lack of knowledge concerning dental trauma issues. Prevention programs and promoting actions among this population are important and should be adopted.